The Impact of EU Law on Private Law - some thoughts on the impact of the non-discrimination principle on private autonomy - Reich, Norbert (Revista Direitos Humanos Fundamentais, 2013)
The paper discusses a new dimension of EU law, namely its impact on private law based on the principle of non-discrimination, thus deliberately going beyond concepts of autonomy and freedom of contract as recognised in all Member States and by the EU itself. Article 21 of the EU Charter of Fundamental Rights has “constitutionalised” this principle which originally found recognition in several EU directives on employment and consumer law analysed in this paper with a special regard to the growing case-law of the Court of Justice of the EU (ECJ).